2017
DOI: 10.1002/uog.17320
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and cost‐effectiveness of different strategies to triage women with adnexal masses: a prospective study

Abstract: In our study sample, SR ± SA seems to be the best strategy to triage women with adnexal masses for surgical management. Among postmenopausal women, SR ± SA + CA 125 increased the NRI at a reasonable extra cost. Our data do not justify the use of HE4 and ROMA in the initial triage of women with adnexal masses. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
(40 reference statements)
1
31
1
Order By: Relevance
“…We were able to find only one paper dealing with the costeffectiveness of HE4 use in the initial triage of women with pelvic masses [74]. While the addition of CA125 to transvaginal US proved useful enough to triage those patients (but only in post-menopausal group), the study did not support the cost-effectiveness of HE4 use in replacing CA125 in the initial triage of adnexal masses (Table 2).…”
Section: He4 Cost-effectivenessmentioning
confidence: 92%
“…We were able to find only one paper dealing with the costeffectiveness of HE4 use in the initial triage of women with pelvic masses [74]. While the addition of CA125 to transvaginal US proved useful enough to triage those patients (but only in post-menopausal group), the study did not support the cost-effectiveness of HE4 use in replacing CA125 in the initial triage of adnexal masses (Table 2).…”
Section: He4 Cost-effectivenessmentioning
confidence: 92%
“…Ovarian cancer (OC) has the highest mortality rate and most unfavourable prognosis among the gynaecological malignancies; the average 5-year survival rate is < 50% (1,2). Currently, transvaginal ultrasound is the most commonly used, noninvasive, affordable imaging technique for pre-operative evaluations of adnexal masses with minimal risk and discomfort to the patient (3)(4)(5). And subjective assessments of ultrasound findings by specialists in gynaecological ultrasonography are one of the best means of evaluating adnexal masses in clinical practice (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Despite our findings, as well as those of other studies that characterize CA125 to be considerably less sensitive and specific than multimodal risk algorithms such as MIA2G or even ultrasound [10] for determining the likelihood of malignancy, the use of CA125 alone to assess women with adnexal findings remains a popular choice in the assessment of women presenting with an adnexal mass. A recent study from Italy by Piovano and colleagues [11] found that adding CA125 and ROMA to triage algorithms for postmenopausal women with adnexal masses improved screening accuracy compared with ultrasound alone; the addition of ROMA was considerably more expensive and provided for minimal additional screening benefit compared with CA125 alone. While economic considerations do play some role in the continued use of CA125 alone for the presurgical assessment of women with adnexal masses, the availability of FDA-cleared multimodal assays and the lack of FDA clearance for the use of CA125 in these clinical situations continue to call into question the ongoing use of a single analyte assay for which there is considerable evidence to support it being an inferior triage process for women presenting with adnexal masses compared with multimodal algorithms [12].…”
Section: Discussionmentioning
confidence: 99%